The Needs of Teaching English Using Brain-Based Learning in 21st Century Era - Winantaka, Binar; Katrina Herda, Rozanah; Sulistyowati, Nina; Margana, Margana; Mukminatun, Siti; Aguilar Principe, Regine; Yingfan, Miao (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background: In the context of 21st-century learning, effective engagement of students and accommodation of many learning styles depend on brain-based learning (BBL). This approach improves understanding, memory, and adaptability by matching instruction with cognitive science and educational needs. Therefore, BBL emphasizes matching teaching approaches to how the brain processes and remembers information, which improves language acquisition, as teaching English entails employing tactics that address cognitive skills such as memory, attention, and motivation. Methodology: This quantitative study involved 50 English teachers in Yogyakarta, Indonesia, aim to reveal the teachers’ needs to teach English using BBL in this 21st-century era. The instrument of data collection was a questionnaire designed using the 5-Likert Scale that was interpreted using mean scores for each statement.Findings: The finding of this study revealed teachers need BBL in applying teaching scenarios, as well as the BBL represents Project-Based learning supported by audiovisual and critical thinking integration during the learning process. All those components are fitted with the characteristics of the balance of the right and left-brain sides.Conclusion: It is deemed essential since it directly affects the instructors' ability to effectively nurture student engagement and achievement, and the teachers should be consulted regarding the need for BBL. Incorporating educators into this conversation also guarantees that the tactics used are realistic and adapted to actual classroom situations. The knowledge and expertise of educators are crucial for improving brain-based learning strategies.Originality: This study can be a pioneer in exploring more opportunities for the needs of BBL and its relationship with learning success. Moreover, knowing brain balance contributes to a more inclusive and effective learning environment by accommodating different learning styles and boosting overall student well-being and academic achievement.